2016
DOI: 10.1186/s13731-016-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in entrepreneurs’ business growth intentions: an identity approach

Abstract: The present empirical study explores the effects of gender role and cultural identity (masculinity and femininity) in mens' and womens' business growth intentions in established firms. A questionnaire survey was completed by 572 business owners (286 females). Results from moderated mediation regression analyses found that masculinity and femininity fully mediated the effects of entrepreneurs' sex on business growth intentions. Females who had higher femininity orientation and independent self-construal reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 61 publications
1
29
0
4
Order By: Relevance
“…This opens the road for researchers to examine other theoretical variables that influence the lower entrepreneurial intention of women, For example Zampetakis et al (2016) proposed that gender identity, that is the extent to which people incorporate gender roles into their self-concepts, is a promising construct for the study of gender differences in intentions related to entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This opens the road for researchers to examine other theoretical variables that influence the lower entrepreneurial intention of women, For example Zampetakis et al (2016) proposed that gender identity, that is the extent to which people incorporate gender roles into their self-concepts, is a promising construct for the study of gender differences in intentions related to entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found that for women who work in gender incongruent occupations dominated by men, the experience of discrimination has a negative association with their well-being ( Maddox, 2013 ; Di Marco et al, 2016 ). Being a member of two traditionally unrelated groups (i.e., being a woman and an entrepreneur) is not an easy task for women ( Zampetakis et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…No nível individual, estudos têm mostrado a importância do empreendedor na promoção do crescimento da empresa, por meio de motivações, intenções e expectativas de crescimento (Lasch, Le Roy, & Yami, 2007;Rasmussen, Ladegard, & Korhonen-Sande, 2016). No entanto, intenções representam apenas a primeira etapa do processo de crescimento (Zampetakis, Bakatsaki, Kafetsios & Moustakis, 2016). Como o empreendedor exerce um papel central no processo de crescimento (Rasmussen et al, 2016), há outros aspectos, além dos motivacionais, que podem influenciar o crescimento de negócios.…”
Section: Introductionunclassified
“…The image of the entrepreneur has traditionally been masculinized and rooted in masculine discourse [75]. Moreover, research has found that for women who work in gender incongruent occupations dominated by men, the experience of discrimination has a negative association with their well-being [76].…”
Section: Comparisons Based On Gendermentioning
confidence: 99%